An Introduction to the Topic ‘Copernicus and Astrology’. A Commentary on the Theses of Robert S. Westman - Michał Kokowski (Studia Historiae Scientiarum)
This article is an introduction to the subject of Copernicus and astrology. It presents an overview of a set of facts and positions of researchers exploring the relevant ideas of Copernicus, as well as the author’s own perspective. A key role is played by a critique of R.S. Westman’s theses.